Extracellular Vesicles in Acute Leukemia: A Mesmerizing Journey With a Focus on Transferred microRNAs - Izadirad, Mehrdad; Huang, Zoufang; Jafari, Farideh; Hamidieh, Amir Ali; Gharehbaghian, Ahmad; Li, Yi-Dong; Jafari, Leila; Chen, Zhe-Sheng (Frontiers in Cell and Developmental Biology, 2021)
Despite their small size, the membrane-bound particles named extracellular vesicles (EVs) seem to play an enormous role in the pathogenesis of acute leukemia. From oncogenic hematopoietic stem cells (HSCs) to become leukemic cells to alter the architecture of bone marrow (BM) microenvironment, EVs are critical components of leukemia development. As a carrier of essential molecules, especially a group of small non-coding RNAs known as miRNA, recently, EVs have attracted tremendous attention as a prognostic factor. Given the importance of miRNAs in the early stages of leukemogenesis and also their critical parts in the development of drug-resistant phenotype, it seems that the importance of EVs in the development of leukemia is more than what is expected. To be familiar with the clinical value of leukemia-derived EVs, this review aimed to briefly shed light on the biology of EVs and to discuss the role of EV-derived miRNAs in the development of acute myeloid leukemia and acute lymphoblastic leukemia. By elaborating the advances and challenges concerning the isolation of EVs, we discuss whether EVs could have a prognostic value in the clinical setting for leukemia.